Oxide materials including zeolitic materials having framework type AEI
Patent Information
- Application Number
- JP2021543167
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-01-23
- Filing Date
- 2020-01-21
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2040-01-21
Smart Images

Figure 0007631206000002 
Figure 0007631206000003 
Figure 0007631206000004
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for the preparation of an oxidic material comprising a zeolitic material having a framework type AEI and a framework structure comprising a tetravalent element Y, a trivalent element X and O, the method comprising preparing a synthesis mixture comprising water, a source of Y, a source of X comprising sodium, an AEI framework directing agent and a source of sodium other than a source of X, heating the synthesis mixture to a temperature in the range of 100-180°C and maintaining the synthesis mixture at this temperature range under autogenous pressure. Furthermore, the present invention relates to an oxidic material obtainable or obtained by said method. Furthermore, the present invention relates to the use of said oxidic material, preferably as a catalytically active material. [Background technology]
[0002] Zeolitic materials having framework type AEI have been used in industrial applications to treat combustion exhaust gases, e.g., to reduce nitrogen oxides (NO x It is known that synthetic AEI zeolitic materials are potentially useful as catalysts or catalyst components for the conversion of zeolitic compounds such as benzene, ...
[0003] WO2016 / 080547A1 discloses a method for producing AEI type zeolites, in which, together with the above-mentioned sources of elements that build the zeolite framework, a further source of sodium is used by addition of an alkali (sodium) source. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] WO2016 / 080547A1 Summary of the Invention [Problem to be solved by the invention]
[0005] According to the present invention, instead of employing a source of a trivalent element such as Al on the one hand and a source of sodium on the other hand, it has been found that it is possible to employ a source of a trivalent element which further contains sodium, thus avoiding at least part of the sodium sources of the prior art. [Means for solving the problem]
[0006] The present invention therefore relates to a method for producing an oxide material comprising a zeolitic material having a framework type AEI and a framework structure comprising a tetravalent element Y, a trivalent element X and O, said method comprising the steps of: (i) preparing a synthesis mixture comprising water, a source of Y, a sodium-containing source of X, an AEI framework directing agent, and a source of sodium other than a source of X; (ii) heating the synthesis mixture from step (i) to a temperature in the range of 100-180° C. and maintaining the synthesis mixture at this temperature range for a time in the range of at least 6 hours under autogenous pressure to obtain in its mother liquor an oxide material comprising a zeolitic material having a framework type AEI and a framework structure comprising a tetravalent element Y, a trivalent element X and an O; Including, wherein the AEI backbone directing agent according to step (i) comprises a N,N-dialkyl-dialkylpiperidinium cation; in the synthesis mixture prepared in step (i) subjected to step (ii), the molar ratio of the source of Y, calculated as YO2, to the source of X, calculated as X2O3, defined as YO2:X2O3, is at least 30:1; In the synthesis mixture prepared in step (i) subjected to step (ii), the molar ratio of sodium, calculated as Na2O, to the source of Y, calculated as YO2, defined as Na2O:YO2, is at least 0.23:1; Y is one or more of Si, Ge, S, Ti, and Zr; X is one or more of Al, B, Ga, and In. [Brief description of the drawings]
[0007] [Figure 1] FIG. 1 shows the NH3-TPD curve according to Comparative Example 1b). [Diagram 2] FIG. 2 shows the NH3-TPD curve according to Example 1c). [Diagram 3] FIG. 3 shows the XRD patterns of the zeolitic materials according to Example 2, Table 1, Runs 6, 11 and 12. [Figure 4] FIG. 4 shows the dependence of the crystallinity of the zeolitic material according to Example 3 on the crystallization time. [Diagram 5] FIG. 5 shows the XRD patterns of the zeolitic material according to Example 3 crystallized for various times. [Figure 6] FIG. 6 shows SEM images of zeolitic materials according to Example 3 crystallized for various times. [Figure 7] FIG. 7 shows the results obtained from the selective catalytic reduction test of Test Example 5. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] The N,N-dialkyl-dialkylpiperidinium cation is preferably a N,N-(C1-C3)dialkyl-(C1-C3)dialkylpiperidinium cation, more preferably a N,N-(C1-C2)dialkyl-(C1-C2)dialkylpiperidinium cation, more preferably the N,N-dialkyl-dialkylpiperidinium cation is selected from the group consisting of a N,N-(C1-C2)dialkyl-2,6-(C1-C2)dialkylpiperidinium cation, a N,N-(C1-C2)dialkyl-3,5-(C1-C2)dialkylpiperidinium cation, and a mixture of two or more thereof, more preferably N,N-dimethyl- It is selected from the group consisting of 2,6-(C1-C2)dialkylpiperidinium cation, N,N-dimethyl-3,5-(C1-C2)dialkylpiperidinium cation, and a mixture of two or more thereof, more preferably selected from the group consisting of N,N-diethyl-2,6-dimethylpiperidinium cation, N,N-diethyl-3,5-dimethylpiperidinium cation, and a mixture thereof, more preferably the N,N-dialkyl-dialkylpiperidinium cation comprises, more preferably consists of, the N,N-diethyl-2,6-dimethylpiperidinium cation, more preferably the N,N-diethyl-cis-2,6-dimethylpiperidinium cation.
[0009] Preferably, the AEI framework directing agent according to step (i) is a salt, more preferably one or more of a hydroxide and a halide, the halide being preferably one or more of an iodide, chloride, fluoride and bromide, and more preferably the AEI framework directing agent according to step (i) comprises a hydroxide, more preferably is a hydroxide.
[0010] Preferably, the AEI backbone directing agent according to step (i) comprises, more preferably consists of, N,N-diethyl-2,6-dimethylpiperidinium hydroxide, more preferably N,N-diethyl-cis-2,6-dimethylpiperidinium hydroxide.
[0011] Preferably, Y comprises Si, more preferably is Si. Preferably, X comprises Al, more preferably is Al. More preferably, Y is Si and X is Al.
[0012] Generally, according to step (i), any suitable source of the tetravalent element Y can be used. Preferably, the source of Y comprises one or more of wet process silica, dry process silica, and colloidal silica. More preferably, the source of Y comprises, and more preferably consists of, colloidal silica.
[0013] Generally, according to step (i), any suitable source of the trivalent element X can be used. Preferably, the source of X is sodium aluminate, more preferably one or more of NaAlO2, NaAl(OH)4, Na2O·Al2O3, Na2Al2O4, Na5AlO4, Na7Al3O8, Na 17 AlO 16 , and NaAl 11 O 17 More preferably, the source of X comprises, and more preferably consists of, NaAlO2.
[0014] Preferably, the source of sodium other than the source of X comprises NaOH, more preferably consists of NaOH.
[0015] The synthesis mixture prepared in step (i) subjected to step (ii) preferably does not contain any zeolitic material having a framework type FAU, more preferably does not contain any zeolitic material having a framework type other than AEI.
[0016] In the synthesis mixture prepared in step (i) subjected to step (ii), the molar ratio of the source of Y, calculated as YO2, to the source of X, calculated as X2O3, defined as YO2:X2O3, is preferably at least 40:1, more preferably at least 50:1, more preferably at least 60:1. Preferably, in the synthesis mixture prepared in step (i) subjected to step (ii), the molar ratio of the source of Y, calculated as YO2, to the source of X, calculated as X2O3, defined as YO2:X2O3, is in the range of 30:1 to 600:1, more preferably in the range of 40:1 to 500:1, more preferably in the range of 50:1 to 300:1, more preferably in the range of 60:1 to 150:1, more preferably in the range of 60:1 to 100:1, more preferably in the range of 60:1 to 80:1.
[0017] In the synthesis mixture prepared in step (i) subjected to step (ii), the molar ratio of the source of Y, calculated as YO2, to the AEI framework directing agent, defined as YO2:SDA, is preferably in the range of 1:1 to 14:1, more preferably in the range of 2:1 to 12:1, more preferably in the range of 4:1 to 10:1, more preferably in the range of 7:1 to 9:1.
[0018] In the synthesis mixture prepared in step (i) subjected to step (ii), the molar ratio of the source of Y, calculated as YO2, to water, defined as YO2:water, is preferably in the range of 0.01:1 to 1:1, more preferably in the range of 0.01:1 to 0.5:1, more preferably in the range of 0.01:1 to 0.1:1, more preferably in the range of 0.01:1 to 0.05:1.
[0019] In the synthesis mixture prepared in step (i) subjected to step (ii), the molar ratio of sodium, calculated as NaO2, to the source of Y, calculated as YO2, defined as NaO2:YO2, is preferably in the range of 0.25:1 to 0.50:1, more preferably in the range of 0.27:1 to 0.45:1, more preferably in the range of 0.29:1 to 0.40:1, more preferably in the range of 0.30:1 to 0.35:1.
[0020] In addition to water, a source of Y, a sodium-containing source of X, an AEI framework directing agent, and a source of sodium other than a source of X, the synthesis mixture prepared in step (i) may comprise one or more further additional components. Preferably, 95-100% by mass, more preferably 98-100% by mass, more preferably 99-100% by mass of the synthesis mixture prepared in step (i) subjected to step (ii) consists of water, a source of Y, a sodium-containing source of X, an AEI framework directing agent, and a source of sodium other than a source of X.
[0021] In step (i) of the process of the present invention, the synthesis mixture prepared in step (i) subjected to step (ii) preferably further comprises a crystalline seed material comprising a zeolitic material having framework type AEI and a framework structure comprising tetravalent element Y, trivalent elements X and O.
[0022] Preferably, 95 to 100% by mass, preferably 98 to 100% by mass, more preferably 99 to 100% by mass of the synthesis mixture prepared in step (i) subjected to step (ii) consists of water, a source of Y, a sodium-containing source of X, an AEI framework directing agent, a source of sodium other than a source of X, and a crystalline seed material.
[0023] Step (ii) of the process of the invention comprises heating the synthesis mixture from step (i) to a temperature in the range of 100-180° C. and maintaining the synthesis mixture at this temperature range for a time in the range of at least 6 hours under autogenous pressure. Preferably, step (ii) is carried out in an autoclave. Preferably, the synthesis mixture prepared in step (i) is heated to the temperature in step (ii) at a heating rate in the range of 0.5-4 K / min, more preferably in the range of 1-3 K / min.
[0024] Preferably, the temperature in step (ii) is in the range of 120 to 160°C, more preferably in the range of 130 to 150°C.
[0025] Preferably, heating the synthesis mixture from step (i) in step (ii) comprises agitating, preferably mechanically agitating, more preferably stirring, the synthesis mixture. Preferably, step (ii) maintains the synthesis mixture at temperature for a period in the range of from 6 to 12 hours, more preferably in the range of from 6 to 10 hours, more preferably in the range of from 7 to 9 hours.
[0026] Since step (ii) of the process of the present invention involves heating the synthesis mixture from step (i) under autogenous pressure, it is preferred that step (ii) further comprises depressurizing the mixture. Either before, during or after depressurization, the process of the present invention preferably further comprises: (iii) cooling the mixture obtained from step (ii) to a temperature preferably in the range of 10 to 50° C., more preferably in the range of 20 to 35° C.; (iv) separating the oxide material comprising the zeolitic material from the mixture resulting from step (ii), said separation preferably comprising: (iv.1) subjecting the mixture obtained from step (ii) to a solid-liquid separation process, preferably comprising filtration or spraying; (iv.2) washing the oxide material, preferably comprising zeolitic material, obtained from step (iv.1); (iv.3) drying the oxide material comprising the zeolitic material from step (iv.1) or from step (iv.2), preferably from step (iv.2), preferably in a gas atmosphere having a temperature in the range of 80-170°C, more preferably in the range of 100-140°C, more preferably in the range of 100-130°C. A process comprising: (v) calcining the oxide material comprising the zeolitic material obtained from step (iv), preferably in a gas atmosphere having a temperature in the range of 400-600° C. Further comprising: Here, at least a portion of the mother liquor obtained by step (iv.1) of separating the oxide material from the mixture obtained from step (ii) is preferably recycled to step (i) as part of the synthesis mixture prepared in step (i).
[0027] Preferably, the gas atmosphere in step (iv.3) comprises oxygen, more preferably air, lean air or synthetic air, and the gas atmosphere in step (v) comprises oxygen, more preferably air, lean air or synthetic air.
[0028] In the method of the present invention, the oxide material comprising a zeolitic material having a framework type AEI and a framework structure comprising a tetravalent element Y, a trivalent element X and O preferably exhibits one or both of the following characteristics (1) to (2), more preferably the following characteristics (1) to (2): (1) an ammonia desorption vs programmed temperature (NH3-TPD) curve (NH3-TPD determined as described in Reference Example 1.5 herein) showing a peak having its maximum at (460±15)°C, preferably at (460±10)°C, more preferably at (460±5)°C, and preferably a further peak having its maximum at (175±15)°C, preferably at (175±10)°C, more preferably at (175±5)°C; (2) 550 to 700 m, as determined as described in Reference Example 1.2 of the present specification. 2 / g, preferably 600 to 660 m 2 / g, more preferably 520 to 640 m 2 / g range of BET specific surface area.
[0029] The method of the invention preferably comprises the steps of: (vi) subjecting the oxide material comprising zeolitic material obtained from step (iv) or step (v), more preferably from step (v), to ion exchange conditions, more preferably ammonium exchange conditions, more preferably comprising contacting the oxide material comprising zeolitic material obtained from step (iv) or step (v), more preferably from step (v), with a solution comprising ammonium ions to obtain an oxide material comprising zeolitic material having framework type AEI in its ammonium form, Further includes:
[0030] The solution comprising ammonium ions according to step (vi) is preferably an aqueous solution comprising dissolved ammonium salts, more preferably dissolved inorganic ammonium salts, more preferably dissolved ammonium nitrate. Preferably, the contacting of the solution with the oxide material comprising zeolitic material according to step (vi) is repeated at least once, more preferably once or twice, more preferably once. Preferably, the contacting of the solution with the oxide material comprising zeolitic material according to step (vi) comprises one or more of impregnating the zeolitic material with the solution and spraying the oxide material comprising zeolitic material with the solution, more preferably impregnating the oxide material comprising zeolitic material with the solution according to step (vi).
[0031] The method of the invention preferably comprises the steps of: (vii) calcining the oxide material comprising zeolitic material obtained from step (vi) to obtain an oxide material comprising zeolitic material in its H form. Further includes:
[0032] Preferably, according to step (vii), the oxide material comprising the zeolitic material is calcined in a gas atmosphere having a temperature in the range of 300 to 700° C., more preferably in the range of 350 to 600° C., more preferably in the range of 400 to 600° C. Preferably, the gas atmosphere comprises oxygen, more preferably air, lean air or synthetic air.
[0033] Depending on the intended use of the oxide material comprising zeolitic material, the material, preferably obtained from step (vii), may be used as is. Furthermore, it is conceivable that the oxide material comprising zeolitic material may be subjected to one or more further post-processing steps. For example, the oxide material comprising zeolitic material, most preferably obtained as a powder, may be suitably processed into a moulded article or shaped body by any suitable method, including but not limited to extrusion, tableting, spraying, etc. Preferably, the shaped body may have a rectangular, triangular, hexagonal, square, oval or circular cross section, and / or is preferably in the form of a star, tablet, sphere, cylinder, strand or hollow cylinder. When preparing the moulded body, one or more binders may be used, which may be selected depending on the intended use of the moulded body. Possible binder materials include, but are not limited to, graphite, silica, titania, zirconia, alumina, and mixed oxides of two or more of silicon, titanium and zirconium. The mass ratio of the oxidic material comprising the zeolitic material to the binder is generally not subject to any particular limitation and may, for example, be in the range of 10:1 to 1:10. According to a further example in which the oxidic material comprising the zeolitic material is used as a catalyst or as a catalyst component for treating, for example, an exhaust gas stream, such as the exhaust gas stream of an engine, the oxidic material comprising the zeolitic material can be used as a component of a washcoat that is applied onto a suitable substrate, such as a wall-flow filter.
[0034] According to a preferred embodiment of the invention, the oxide material comprising a zeolitic material is subjected to a post-treatment comprising supporting a metal M on the zeolitic material contained in the oxide material. The invention therefore more preferably relates to a method as described above, which method comprises the steps of: (viii) supporting the metal M on the zeolitic material contained in the oxide material, preferably on the zeolitic material contained in the oxide material obtained from step (vi) or step (vii); Further includes:
[0035] With regard to step (viii), it is preferable that step (viii) is (viii.1) preparing a mixture comprising an oxide material comprising a zeolitic material, preferably obtained from step (vi) or step (vii), a source of metal M, a solvent for the source of metal M and optionally an acid, preferably an organic acid, preferably wherein the solvent comprises water, preferably wherein the source of metal M comprises a salt of metal M and preferably wherein the acid comprises acetic acid, (viii.2) heating the mixture prepared in step (viii.1) to a temperature in the range of 30 to 90° C., preferably in the range of 40 to 80° C., (viii.3) preferably cooling, more preferably quenching, the mixture obtained from step (viii.2), (viii.4) separating the oxide material comprising the zeolitic material comprising the metal M from the mixture obtained from step (viii.2) or (viii.3), preferably from step (viii.3), wherein the separation preferably comprises washing the oxide material comprising the zeolitic material comprising the metal M, (viii.5) drying the oxide material comprising the zeolitic material comprising metal M obtained from step (viii.4) in a gas atmosphere, preferably at a temperature of the gas atmosphere in the range of 90-200°C, more preferably in the range of 100-150°C, preferably the gas atmosphere comprising oxygen, (viii.6) preferably calcining the oxide material comprising the zeolitic material comprising metal M obtained from step (viii.4) or step (viii.5), preferably from step (viii.5), in a gas atmosphere, preferably at a temperature of the gas atmosphere in the range of 350-600°C, more preferably in the range of 450-600°C, preferably wherein the gas atmosphere comprises oxygen, It is preferred that the compound contains
[0036] With regard to the metal M in step (viii), preferably, the metal M is a transition metal of groups 7 to 12 of the periodic system of the elements. More preferably, the metal M is one or more of Fe, Co, Ni, Cu, and Zn, more preferably one or more of Fe and Cu, more preferably, the metal M comprises Cu, more preferably is Cu. Preferably, by step (viii), the metal M is supported on the zeolitic material in an amount, calculated as MO, in the range of 0.1 to 15 mass %, more preferably in the range of 0.5 to 10 mass %, more preferably in the range of 1 to 7 mass %, more preferably in the range of 1.5 to 6 mass %, more preferably in the range of 2 to 3 mass %, based on the total mass of the zeolitic material.
[0037] Preferably, more than 50 mass%, more preferably 55 to 100 mass%, more preferably 60 to 100 mass%, more preferably 65 to 100 mass%, more preferably 70 to 100 mass%, more preferably 75 to 100 mass%, more preferably 80 to 100 mass%, more preferably 85 to 100 mass%, more preferably 90 to 100 mass%, more preferably 95 to 100 mass%, more preferably 98 to 100 mass%, and more preferably 99 to 100 mass% of the obtained oxide material consists of a zeolite material having a framework type AEI optionally containing Cu.
[0038] The present invention further relates to an oxide material comprising a zeolitic material having framework type AEI and having a framework structure comprising a tetravalent element Y and a trivalent element X and O, obtainable or obtained or produceable or produced by the method described herein above, wherein the oxide material is preferably more than 50% by weight, more preferably 55-100% by weight, more preferably 60-100% by weight, more preferably 65-100% by weight, more preferably 70-100% by weight, more preferably 75-100% by weight, more preferably 80-100% by weight, more preferably 85-100% by weight, more preferably 90-100% by weight, more preferably 95-100% by weight, more preferably 10 ... 100% by mass, more preferably 98 to 100% by mass, more preferably 99 to 100% by mass, of the oxide material consists of a zeolitic material having a framework type AEI, and the oxide material optionally comprises one or more further zeolitic materials having a framework type other than AEI and having a framework structure comprising a tetravalent element Y and a trivalent element X and O, the further zeolitic materials preferably having framework type MOR or ANA, and preferably 95 to 100% by mass, more preferably 98 to 100% by mass, more preferably 99 to 100% by mass of the oxide material consists of a zeolitic material having a framework type AEI and optionally one or more zeolitic materials having a framework type other than AEI.
[0039] The present invention still further relates to an oxide material comprising a zeolitic material comprising a metal M, having framework type AEI and having a framework structure comprising a tetravalent element Y and a trivalent element X and O, obtainable or obtained or produceable or produced by the method described herein above, wherein the zeolitic material comprises preferably more than 50% by weight, more preferably 55-100% by weight, more preferably 60-100% by weight, more preferably 65-100% by weight, more preferably 70-100% by weight, more preferably 75-100% by weight, more preferably 80-100% by weight, more preferably 85-100% by weight, more preferably 90-100% by weight, more preferably 95-100% by weight, more preferably 10 ... Preferably, 5 to 100% by mass, more preferably 98 to 100% by mass, more preferably 99 to 100% by mass of the oxide material is composed of a zeolitic material having a framework type AEI containing Cu, and the oxide material optionally comprises one or more further zeolitic materials having a framework type other than AEI and having a framework structure containing a tetravalent element Y and a trivalent element X and O, the further zeolitic materials preferably having a framework type MOR or ANA, and preferably 95 to 100% by mass, more preferably 98 to 100% by mass, more preferably 99 to 100% by mass of the oxide material is composed of a zeolitic material having a framework type AEI and optionally one or more zeolitic materials having a framework type other than AEI.
[0040] The present invention still further relates to an oxide material comprising a zeolitic material having framework type AEI and having a framework structure comprising a tetravalent element Y and a trivalent element X and O, said zeolitic material exhibiting an ammonia desorption vs programmed temperature (NH3-TPD) curve showing a peak having its maximum at (460±15)°C, preferably at (460±10)°C, more preferably at (460±5)°C, and preferably a further peak having its maximum at (175±15)°C, preferably at (175±10)°C, more preferably at (175±5)°C, wherein NH3-TPD is determined as described in Reference Example 1.5 herein, Y is one or more of Si, Ge, S, Ti, and Zr; X is one or more of Al, B, Ga, and In; Preferably more than 50% by mass, more preferably 55 to 100% by mass, more preferably 60 to 100% by mass, more preferably 65 to 100% by mass, more preferably 70 to 100% by mass, more preferably 75 to 100% by mass, more preferably 80 to 100% by mass, more preferably 85 to 100% by mass, more preferably 90 to 100% by mass, more preferably 95 to 100% by mass, more preferably 98 to 100% by mass, and more preferably 99 to 100% by mass of the oxide material is made of a zeolite material having an AEI framework. The oxide material optionally comprises one or more further zeolitic materials having a framework type other than AEI and having a framework structure comprising a tetravalent element Y and a trivalent element X and O, the further zeolitic materials preferably having framework type MOR or ANA, and preferably 95-100% by mass, more preferably 98-100% by mass, more preferably 99-100% by mass of the oxide material consists of zeolitic materials having framework type AEI and optionally one or more zeolitic materials having framework types other than AEI.
[0041] In the oxide materials described herein above, preferably, Y comprises Si, more preferably, it is Si. Preferably, X comprises Al, more preferably, it is Al. More preferably, Y is Si and X is Al.
[0042] In the framework structure of the zeolitic material having framework type AEI, the molar ratio of Y, calculated as YO2, to X, calculated as X2O3, defined as YO2:X2O3, is preferably at least 10: 1. Preferably, in the framework structure of the zeolitic material having framework type AEI, the molar ratio of Y, calculated as YO2, to X, calculated as X2O3, defined as YO2:X2O3, is in the range of 10:1 to 25:1, more preferably in the range of 11:1 to 20:1, more preferably in the range of 12:1 to 18:1.
[0043] Preferably, the oxide material has a viscosity of 550 to 700 nm, as determined as described in Reference Example 1.2 herein. 2 / g, more preferably 600 to 660m 2 / g, more preferably 620 to 640m 2 / g. Preferably, 95-100% by weight, preferably 98-100% by weight, more preferably 99-100% by weight of the zeolitic material having framework type AEI consists of Y, X, O and optionally H. Preferably, the oxide material is obtainable or obtained or can be produced or has been produced by a method as described herein above.
[0044] Preferably, the oxide material further comprises a metal M, preferably a transition metal of groups 7 to 12 of the periodic system of elements, more preferably at least one of Fe, Co, Ni, Cu, and Zn, more preferably at least one of Fe and Cu, more preferably the metal M comprises Cu, more preferably is Cu. In general, it is contemplated that the metal M comprises a noble metal, more preferably a platinum group metal, more preferably the metal M comprises Pd and / or Pt. Preferably, the metal M is included in an amount calculated as MO in the range of 0.1 to 15 mass %, more preferably in the range of 0.5 to 10 mass %, more preferably in the range of 1 to 7 mass %, more preferably in the range of 1.5 to 6 mass %, more preferably in the range of 2 to 3 mass %, based on the total mass of the oxide material, and preferably the metal M is included in a zeolitic material included in the oxide material. Preferably, 95-100% by weight, more preferably 98-100% by weight, more preferably 99-100% by weight of the zeolitic material having framework type AEI contained in the oxide material consists of Y, X, O, the metal M, and optionally H. Preferably, the oxide material comprising the zeolitic material comprising the metal M is obtainable or obtained or can be produced or has been produced by a method as described herein above.
[0045] The oxide material comprising the zeolitic material of the present invention, having framework type AEI and having a framework structure comprising tetravalent element Y and trivalent elements X and O, can be used for any conceivable purpose, including but not limited to, absorbent, molecular sieve, catalytically active material, catalyst, or catalyst component, more preferably as catalytically active material, catalyst, or catalyst component. Preferably, the oxide material comprising the zeolitic material of the present invention is used for the conversion of C1 compounds to one or more olefins, more preferably for the conversion of methanol to one or more olefins, or for the conversion of synthesis gas comprising carbon monoxide and hydrogen to one or more olefins. Furthermore, the oxide material comprising the zeolitic material of the present invention can be used for dehydrogenation. Preferably, the oxide material for said use as described above is an oxide material obtainable or obtained or can be produced or produced by the method as described herein above, or the oxide material for said use as described above is an oxide material obtainable or obtained or can be produced or produced by the method as described herein above, which exhibits ammonia desorption vs programmed temperature (NH3-TPD) curve as defined herein above. More preferably, the oxide material comprising the zeolitic material of the present invention is used for the selective catalytic reduction of nitrogen oxides in an exhaust gas stream, more preferably an exhaust gas stream from a diesel engine. Preferably, the oxide material for said use as described above is an oxide material comprising a zeolitic material comprising a metal M, obtainable or obtained or produceable or produced by a method as described herein above.
[0046] The present invention also relates to a process for catalytically converting C1 compounds to one or more olefins, preferably methanol to one or more olefins or a synthesis gas comprising carbon monoxide and hydrogen to one or more olefins, comprising contacting said C1 compounds with a catalyst comprising an oxide material according to the invention. Preferably, the oxide material used in said process is an oxide material obtainable or obtained or produceable or produced by the process described herein above, or the oxide material used in said process is an oxide material obtainable or obtained or produceable or produced by the process described herein above, which exhibits an ammonia desorption vs programmed temperature (NH3-TPD) curve as defined herein above.
[0047] The present invention also relates to a method for catalytically converting C1 compounds to one or more olefins, preferably methanol to one or more olefins or a synthesis gas comprising carbon monoxide and hydrogen to one or more olefins, comprising producing an oxide material comprising a zeolitic material having framework type AEI and a framework structure comprising tetravalent element Y and trivalent elements X and O by a method according to the invention, and contacting said C1 compounds with a catalyst comprising said oxide material. Preferably, said method comprises producing an oxide material comprising a zeolitic material having framework type AEI and a framework structure comprising tetravalent element Y and trivalent elements X and O by a method according to the invention comprising steps (i) and (ii), preferably further comprising one or more of steps (iii) to (vii) as defined herein above for the method of the invention, and contacting said C1 compounds with a catalyst comprising said oxide material.
[0048] The present invention further relates to a method for the selective catalytic reduction of nitrogen oxides in an exhaust gas stream, preferably an exhaust gas stream from a diesel engine, said method comprising contacting said exhaust gas stream with a catalyst comprising an oxide material according to the present invention. Preferably, the oxide material used in said method is an oxide material comprising a zeolitic material comprising a metal M, obtainable or obtained or produceable or produced by a method as described herein above.
[0049] The present invention still further relates to a method for selective catalytic reduction of nitrogen oxides in an exhaust gas stream, preferably an exhaust gas stream from a diesel engine, comprising producing an oxide material comprising a zeolitic material having framework type AEI and having a framework structure comprising tetravalent element Y and trivalent elements X and O by a method according to the invention, and contacting said exhaust gas stream with a catalyst comprising said oxide material. Preferably, said method comprises producing an oxide material comprising a zeolitic material having framework type AEI and having a framework structure and tetravalent element Y and trivalent elements X and O by a method according to the invention, which method comprises supporting a metal M on the zeolitic material contained in the oxide material by step (viii), and contacting said exhaust gas stream with a catalyst comprising said oxide material.
[0050] The present invention further relates to a catalyst, preferably for the selective catalytic reduction of nitrogen oxides in an exhaust gas stream, preferably an exhaust gas stream from a diesel engine, or for the catalytic conversion of C1 compounds to one or more olefins, preferably for the conversion of methanol to one or more olefins, or for the conversion of a synthesis gas comprising carbon monoxide and hydrogen to one or more olefins, said catalyst comprising an oxide material according to the present invention.
[0051] The present invention is further described by the following embodiments and combinations of embodiments, which are indicated by each dependent reference and back reference. In particular, in each case where a range of embodiments is mentioned, it is intended that all embodiments within this range are clearly disclosed to those skilled in the art, for example, in the context of a term such as "the method according to any one of embodiments 1 to 4", i.e., the wording of this term is understood by those skilled in the art as being synonymous with "the method according to any one of embodiments 1, 2, 3 and 4".
[0052] 1. A method for producing an oxide material comprising a zeolitic material having a framework type AEI and a framework structure comprising a tetravalent element Y, a trivalent element X and O, comprising: (i) preparing a synthesis mixture comprising water, a source of Y, a sodium-containing source of X, an AEI framework directing agent, and a source of sodium other than a source of X; (ii) heating the synthesis mixture from step (i) to a temperature in the range of 100-180° C. and maintaining the synthesis mixture at this temperature range for a time in the range of at least 6 hours under autogenous pressure to obtain in its mother liquor an oxide material comprising a zeolitic material having a framework type AEI and a framework structure comprising a tetravalent element Y, a trivalent element X and an O; Including, wherein the AEI backbone directing agent according to step (i) comprises a N,N-dialkyl-dialkylpiperidinium cation; in the synthesis mixture prepared in step (i) subjected to step (ii), the molar ratio of the source of Y, calculated as YO2, to the source of X, calculated as X2O3, defined as YO2:X2O3, is at least 30:1; In the synthesis mixture prepared in step (i) subjected to step (ii), the molar ratio of sodium, calculated as Na2O, to the source of Y, calculated as YO2, defined as Na2O:YO2, is at least 0.23:1; Y is one or more of Si, Ge, S, Ti, and Zr; The method, wherein X is one or more of Al, B, Ga, and In.
[0053] 2. The N,N-dialkyl-dialkylpiperidinium cation is an N,N-(C1-C3)dialkyl-(C1-C3)dialkylpiperidinium cation, preferably an N,N-(C1-C2)dialkyl-(C1-C2)dialkylpiperidinium cation, more preferably an N,N-dialkyl-dialkylpiperidinium cation selected from the group consisting of an N,N-(C1-C2)dialkyl-2,6-(C1-C2)dialkylpiperidinium cation, an N,N-(C1-C2)dialkyl-3,5-(C1-C2)dialkylpiperidinium cation, and a mixture of two or more thereof, more preferably an N,N-dimethyl-2,6-(C1-C2)dialkylpiperidinium cation. The method according to embodiment 1, wherein the N,N-dialkyl-dialkylpiperidinium cation is selected from the group consisting of dialkylpiperidinium cation, N,N-dimethyl-3,5-(C1-C2)dialkylpiperidinium cation, and a mixture of two or more thereof, more preferably selected from the group consisting of N,N-diethyl-2,6-dimethylpiperidinium cation, N,N-diethyl-3,5-dimethylpiperidinium cation, and a mixture thereof, more preferably the N,N-dialkyl-dialkylpiperidinium cation comprises, more preferably consists of, the N,N-diethyl-2,6-dimethylpiperidinium cation, more preferably the N,N-diethyl-cis-2,6-dimethylpiperidinium cation.
[0054] 3. The method according to embodiment 1 or 2, wherein the AEI framework directing agent according to step (i) is a salt, preferably one or more of a hydroxide and a halide, the halide being preferably one or more of an iodide, a chloride, a fluoride and a bromide, more preferably the AEI framework directing agent according to step (i) comprises a hydroxide, more preferably is a hydroxide.
[0055] 4. The method according to any one of the preceding embodiments, wherein the AEI backbone directing agent according to step (i) comprises, preferably consists of, N,N-diethyl-2,6-dimethylpiperidinium hydroxide, preferably N,N-diethyl-cis-2,6-dimethylpiperidinium hydroxide.
[0056] 5. The method of any one of the preceding claims, wherein Y comprises, preferably is, Si.
[0057] 6. The method of any one of the preceding claims, wherein X comprises Al, preferably Al.
[0058] 7. The method of any one of the preceding embodiments, wherein Y is Si and X is Al.
[0059] 8. The method of any one of the preceding claims, wherein the source of Y comprises one or more of wet process silica, dry process silica, and colloidal silica.
[0060] 9. The method of embodiment 8, wherein the source of Y comprises, preferably consists of, colloidal silica.
[0061] 10. The source of X is sodium aluminate, preferably one or more of NaAlO2, NaAl(OH)4, Na2O·Al2O3, Na2Al2O4, Na5AlO4, Na7Al3O8, Na 17 AlO 16 , and NaAl 11 O 17 10. The method of any one of embodiments 1 to 9, comprising:
[0062] 11. The method of any one of the preceding claims, wherein the source of X comprises, and preferably consists of, NaAlO2.
[0063] 12. The method of any one of the preceding claims, wherein the source of sodium other than the source of X comprises, and preferably consists of, NaOH.
[0064] 13. The method according to any one of the preceding claims, wherein the synthesis mixture prepared in step (i) subjected to step (ii) does not contain any zeolitic material having a framework type FAU, preferably does not contain any zeolitic material having a framework type other than AEI.
[0065] 14. The method according to any one of the preceding claims, wherein in the synthesis mixture prepared in step (i) and subjected to step (ii), the molar ratio of the source of Y, calculated as YO2, to the source of X, calculated as X2O3, defined as YO2:X2O3, is at least 40:1, preferably at least 50:1, more preferably at least 60:1.
[0066] 15. The process according to embodiment 14, wherein in the synthesis mixture prepared in step (i) subjected to step (ii), the molar ratio of the source of Y, calculated as YO2, to the source of X, calculated as X2O3, defined as YO2:X2O3, is in the range of 30:1 to 600:1, preferably in the range of 40:1 to 500:1, more preferably in the range of 50:1 to 300:1, more preferably in the range of 60:1 to 150:1, more preferably in the range of 60:1 to 100:1, more preferably in the range of 60:1 to 80:1.
[0067] 16. The method according to any one of the preceding claims, wherein in the synthesis mixture prepared in step (i) subjected to step (ii), the molar ratio of the source of Y, calculated as YO2, to the AEI framework directing agent, defined as YO2:SDA, is in the range of 1:1 to 14:1, preferably in the range of 2:1 to 12:1, more preferably in the range of 4:1 to 10:1, more preferably in the range of 7:1 to 9:1.
[0068] 17. The method according to any one of the preceding embodiments, wherein in the synthesis mixture prepared in step (i) and subjected to step (ii), the molar ratio of the source of Y, calculated as YO2, to water, defined as YO2:water, is in the range of 0.01:1 to 1:1, preferably in the range of 0.01:1 to 0.5:1, more preferably in the range of 0.01:1 to 0.1:1, more preferably in the range of 0.01:1 to 0.05:1.
[0069] 18. The method according to any one of the preceding claims, wherein in the synthesis mixture prepared in step (i) and subjected to step (ii), the molar ratio of sodium, calculated as NaO2, to the source of Y, calculated as YO2, defined as NaO2:YO2, is in the range of 0.25:1 to 0.50:1, preferably in the range of 0.27:1 to 0.45:1, more preferably in the range of 0.29:1 to 0.40:1, more preferably in the range of 0.30:1 to 0.35:1.
[0070] 19. The method according to any one of the preceding claims, wherein 95-100% by weight, preferably 98-100% by weight, more preferably 99-100% by weight, of the synthesis mixture prepared in step (i) subjected to step (ii) consists of water, a source of Y, a sodium-containing source of X, an AEI framework directing agent, and a source of sodium other than a source of X.
[0071] 20. The method of any one of the preceding claims, wherein the synthesis mixture prepared in step (i) and subjected to step (ii) further comprises a crystalline seed material comprising a zeolitic material having framework type AEI and a framework structure comprising tetravalent element Y, trivalent elements X and O.
[0072] 21. The method according to any one of the preceding claims, wherein 95-100% by weight, preferably 98-100% by weight, more preferably 99-100% by weight, of the synthesis mixture prepared in step (i) subjected to step (ii) consists of water, a source of Y, a sodium-containing source of X, an AEI framework directing agent, a source of sodium other than a source of X, and a crystalline seed material.
[0073] 22. The method of any one of the preceding embodiments, wherein step (ii) is carried out in an autoclave.
[0074] 23. The method according to any one of the preceding embodiments, wherein the synthesis mixture prepared in step (i) is heated to the temperature in step (ii) at a heating rate in the range of 0.5 to 4 K / min, preferably in the range of 1 to 3 K / min.
[0075] 24. The method according to any one of the preceding embodiments, wherein the temperature in step (ii) is in the range of 120 to 160°C, preferably in the range of 130 to 150°C.
[0076] 25. The method of any one of the preceding embodiments, wherein, according to step (ii), the synthesis mixture is agitated, preferably mechanically agitated, more preferably stirred.
[0077] 26. The method according to any one of the preceding embodiments, wherein, according to step (ii), the synthesis mixture is maintained at the temperature for a period in the range of 6 to 12 hours, preferably in the range of 6 to 10 hours, more preferably in the range of 7 to 9 hours.
[0078] 27. (iii) cooling the mixture obtained from step (ii) to a temperature preferably in the range of 10 to 50°C, more preferably in the range of 20 to 35°C; (iv) separating the oxide material comprising the zeolitic material from the mixture resulting from step (ii), said separation preferably comprising: (iv.1) subjecting the mixture obtained from step (ii) to a solid-liquid separation process, preferably comprising filtration or spraying; (iv.2) washing the oxide material, preferably comprising zeolitic material, obtained from step (iv.1); (iv.3) drying the oxide material comprising the zeolitic material from step (iv.1) or from step (iv.2), preferably from step (iv.2), preferably in a gas atmosphere having a temperature in the range of 80-170°C, preferably in the range of 100-140°C, more preferably in the range of 100-130°C. A process comprising: (v) calcining the oxide material comprising the zeolitic material obtained from step (iv), preferably in a gas atmosphere having a temperature in the range of 400-600° C. Further comprising: 27. The method according to any one of the preceding claims, wherein at least a portion of the mother liquor obtained by step (iv.1) of separating the oxide material from the mixture obtained from step (ii) is preferably recycled to step (i) as part of the synthesis mixture prepared in step (i).
[0079] 28. The method of embodiment 27, wherein the gas atmosphere in step (iv.3) comprises oxygen, preferably air, lean air, or synthetic air, and the gas atmosphere in step (v) comprises oxygen, preferably air, lean air, or synthetic air.
[0080] 29. An oxide material comprising a zeolitic material having a framework type AEI and a framework structure containing a tetravalent element Y, a trivalent element X, and O, having one or both of the following characteristics (1) to (2), preferably the following characteristics (1) to (2): (1) an ammonia desorption vs programmed temperature (NH3-TPD) curve (NH3-TPD determined as described in Reference Example 1.5 herein) showing a peak having its maximum at (460±15)°C, preferably at (460±10)°C, more preferably at (460±5)°C, and preferably a further peak having its maximum at (175±15)°C, preferably at (175±10)°C, more preferably at (175±5)°C; (2) 550 to 700 m, as determined as described in Reference Example 1.2 of the present specification. 2 / g, preferably 600 to 660 m 2 / g, more preferably 520 to 640 m 2 BET specific surface area in the range of / g The method according to any one of embodiments 1 to 28, preferably embodiment 27 or 28, wherein
[0081] 30. (vi) subjecting the oxide material comprising zeolitic material obtained from step (iv) or step (v), preferably from step (v), to ion exchange conditions, preferably ammonium exchange conditions, more preferably comprising contacting the oxide material comprising zeolitic material obtained from step (iv) or step (v), more preferably from step (v), with a solution comprising ammonium ions to obtain an oxide material comprising zeolitic material having framework type AEI in its ammonium form, 30. The method of any one of embodiments 27 to 29, further comprising:
[0082] 31. The method of embodiment 30, wherein the solution comprising ammonium ions according to step (vi) is an aqueous solution comprising dissolved ammonium salt, preferably dissolved inorganic ammonium salt, more preferably dissolved ammonium nitrate.
[0083] 32. The method of embodiment 30 or 31, wherein contacting the solution with the oxide material comprising the zeolitic material according to step (vi) is repeated at least once, preferably once or twice, more preferably once.
[0084] 33. The method of any one of embodiments 30 to 32, wherein contacting the solution with the oxide material comprising the zeolitic material comprises one or more of impregnating the zeolitic material with the solution and spraying the oxide material comprising the zeolitic material with the solution, according to step (vi), preferably impregnating the oxide material comprising the zeolitic material with the solution.
[0085] 34. (vii) calcining the oxide material comprising zeolitic material obtained from step (vi) to obtain an oxide material comprising zeolitic material in its H form. 34. The method of any one of embodiments 30 to 33, further comprising:
[0086] 35. The method according to embodiment 34, wherein according to step (vii), the oxide material comprising the zeolitic material is calcined in a gas atmosphere having a temperature in the range of 300 to 700°C, preferably in the range of 350 to 600°C, more preferably in the range of 400 to 600°C.
[0087] 36. The method of embodiment 35, wherein the gas atmosphere contains oxygen, preferably air, rare air, or synthetic air.
[0088] 37. (viii) supporting metal M on the zeolitic material contained in the oxide material, preferably on the zeolitic material contained in the oxide material obtained from step (vi) or step (vii). The method according to any one of embodiments 1 to 36, preferably any one of embodiments 33 to 36, more preferably any one of embodiments 30 to 33, further comprising:
[0089] 38. Step (viii) comprises: (viii.1) preparing a mixture comprising an oxide material comprising a zeolitic material, preferably obtained from step (vi) or step (vii), a source of metal M, a solvent for the source of metal M and optionally an acid, preferably an organic acid, preferably wherein the solvent comprises water, preferably wherein the source of metal M comprises a salt of metal M and preferably wherein the acid comprises acetic acid, (viii.2) heating the mixture prepared in step (viii.1) to a temperature in the range of 30 to 90° C., preferably in the range of 40 to 80° C., (viii.3) preferably cooling, more preferably quenching, the mixture obtained from step (viii.2), (viii.4) separating the oxide material comprising the zeolitic material comprising the metal M from the mixture obtained from step (viii.2) or (viii.3), preferably from step (viii.3), wherein the separation preferably comprises washing the oxide material comprising the zeolitic material comprising the metal M, (viii.5) drying the oxide material comprising the zeolitic material comprising metal M obtained from step (viii.4) in a gas atmosphere, preferably at a temperature of the gas atmosphere in the range of 90-200°C, more preferably in the range of 100-150°C, preferably the gas atmosphere comprising oxygen, (viii.6) preferably calcining the oxide material comprising the zeolitic material comprising metal M obtained from step (viii.4) or step (viii.5), preferably from step (viii.5), in a gas atmosphere, preferably at a temperature of the gas atmosphere in the range of 350-600°C, more preferably in the range of 450-600°C, preferably wherein the gas atmosphere comprises oxygen, 38. The method of embodiment 37, comprising:
[0090] 39. The method of embodiment 37 or 38, wherein the metal M is a transition metal of groups 7 to 12 of the Periodic System of the Elements.
[0091] 40. The method of embodiment 39, wherein the metal M is one or more of Fe, Co, Ni, Cu, and Zn, preferably one or more of Fe and Cu, more preferably the metal M comprises Cu, more preferably it is Cu.
[0092] 41. The method according to any one of embodiments 37 to 40, wherein in step (viii) the metal M is supported on the zeolitic material in an amount in the range of 0.1 to 15% by weight, preferably in the range of 0.5 to 10% by weight, more preferably in the range of 1 to 7% by weight, more preferably in the range of 1.5 to 6% by weight, more preferably in the range of 2 to 3% by weight, calculated as MO, based on the total weight of the zeolitic material.
[0093] 42. The process according to any one of the preceding embodiments, wherein more than 50% by weight, preferably 55-100% by weight, more preferably 60-100% by weight, more preferably 65-100% by weight, more preferably 70-100% by weight, more preferably 75-100% by weight, more preferably 80-100% by weight, more preferably 85-100% by weight, more preferably 90-100% by weight, more preferably 95-100% by weight, more preferably 98-100% by weight, more preferably 99-100% by weight of the obtained oxide material consists of zeolitic material having framework type AEI, optionally containing Cu.
[0094] 43. An oxide material comprising a zeolitic material having framework type AEI and having a framework structure comprising a tetravalent element Y and a trivalent element X and O, obtainable or obtained or produceable or produced by the method according to any one of embodiments 1 to 36, wherein the oxide material comprises preferably more than 50% by weight, more preferably 55-100% by weight, more preferably 60-100% by weight, more preferably 65-100% by weight, more preferably 70-100% by weight, more preferably 75-100% by weight, more preferably 80-100% by weight, more preferably 85-100% by weight, more preferably 90-100% by weight, more preferably 95-100% by weight of the oxide material. %, more preferably 98 to 100% by mass, more preferably 99 to 100% by mass of the oxide material consists of zeolitic materials having a framework type AEI and optionally one or more further zeolitic materials having a framework type other than AEI and having a framework structure comprising a tetravalent element Y and a trivalent element X and O, said further zeolitic materials preferably having framework type MOR or ANA, and preferably 95 to 100% by mass, more preferably 98 to 100% by mass, more preferably 99 to 100% by mass of the oxide material consists of zeolitic materials having a framework type AEI and optionally one or more zeolitic materials having a framework type other than AEI.
[0095] 44. An oxide material comprising a zeolitic material comprising a metal M, having a framework type AEI and having a framework structure comprising a tetravalent element Y, a trivalent element X and O, obtainable or obtained or produceable or produced by the method according to any one of embodiments 37 to 42, wherein the zeolitic material comprises preferably more than 50% by weight, more preferably 55 to 100% by weight, more preferably 60 to 100% by weight, more preferably 65 to 100% by weight, more preferably 70 to 100% by weight, more preferably 75 to 100% by weight, more preferably 80 to 100% by weight, more preferably 85 to 100% by weight, more preferably 90 to 100% by weight, more preferably 95 to 100% by weight, of the oxide material. % by mass, more preferably 98 to 100% by mass, more preferably 99 to 100% by mass of the oxide material is composed of a zeolitic material having a framework type AEI containing Cu, said oxide material optionally comprising one or more further zeolitic materials having a framework type other than AEI and having a framework structure comprising a tetravalent element Y and a trivalent element X and O, said further zeolitic materials preferably having a framework type MOR or ANA, and preferably 95 to 100% by mass, more preferably 98 to 100% by mass, more preferably 99 to 100% by mass of the oxide material is composed of a zeolitic material having a framework type AEI and optionally one or more zeolitic materials having a framework type other than AEI.
[0096] 45. An oxide material comprising a zeolitic material having framework type AEI and having a framework structure comprising a tetravalent element Y and a trivalent element X and O, said zeolitic material exhibiting an ammonia desorption vs programmed temperature (NH3-TPD) curve showing a peak having its maximum at (460±15)°C, preferably (460±10)°C, more preferably (460±5)°C, and preferably a further peak having its maximum at (175±15)°C, preferably (175±10)°C, more preferably (175±5)°C, wherein NH3-TPD is determined as described in Reference Example 1.5 herein; Y is one or more of Si, Ge, S, Ti, and Zr; X is one or more of Al, B, Ga, and In; Preferably more than 50% by mass, more preferably 55 to 100% by mass, more preferably 60 to 100% by mass, more preferably 65 to 100% by mass, more preferably 70 to 100% by mass, more preferably 75 to 100% by mass, more preferably 80 to 100% by mass, more preferably 85 to 100% by mass, more preferably 90 to 100% by mass, more preferably 95 to 100% by mass, more preferably 98 to 100% by mass, and more preferably 99 to 100% by mass of the oxide material is made of a zeolite material having an AEI framework, The oxide material optionally comprises one or more further zeolitic materials having a framework type other than AEI and having a framework structure comprising a tetravalent element Y and a trivalent element X and O, the further zeolitic materials preferably having framework type MOR or ANA, and preferably 95 to 100% by mass, more preferably 98 to 100% by mass, more preferably 99 to 100% by mass of the oxide material consists of zeolitic materials having framework type AEI and optionally one or more zeolitic materials having framework types other than AEI.
[0097] 46. The oxide material of embodiment 45, wherein Y comprises, and is preferably, Si.
[0098] 47. The oxide material of embodiment 45 or 46, wherein X comprises Al, preferably is Al.
[0099] 48. The oxide material of any one of embodiments 45 to 47, wherein Y is Si and X is Al.
[0100] 49. The oxide material of any one of embodiments 45 to 48, wherein in the framework structure of the zeolitic material having framework type AEI, the molar ratio of Y, calculated as YO2, to X, calculated as X2O3, defined as YO2:X2O3, is at least 10:1.
[0101] 50. The oxide material according to embodiment 49, wherein in the framework structure of the zeolitic material having framework type AEI, the molar ratio of Y, calculated as YO2, to X, calculated as X2O3, defined as YO2:X2O3, is in the range of 10:1 to 25:1, preferably in the range of 11:1 to 20:1, more preferably in the range of 12:1 to 18:1.
[0102] 51. 550-700 m, as determined as described in Reference Example 1.2 herein. 2 / g, preferably 600 to 660 m 2 / g, more preferably 620 to 640m 2 51. The oxide material of any one of embodiments 45 to 50, exhibiting a BET specific surface area in the range of n / g.
[0103] 52. The oxide material according to any one of embodiments 45 to 51, wherein 95 to 100% by weight, preferably 98 to 100% by weight, more preferably 99 to 100% by weight, of the zeolitic material having framework type AEI consists of Y, X, O and optionally H.
[0104] 53. The oxide material of any one of embodiments 45 to 52, which is the oxide material of embodiment 43.
[0105] 54. The oxide material according to any one of embodiments 45 to 51, further comprising a metal M, preferably a transition metal from groups 7 to 12 of the periodic system of the elements, more preferably one or more of Fe, Co, Ni, Cu, and Zn, more preferably one or more of Fe and Cu, wherein the metal M comprises Cu, more preferably is Cu.
[0106] 55. An oxide material according to embodiment 54, comprising metal M in an amount, calculated as MO, in the range of 0.1 to 15 mass %, preferably in the range of 0.5 to 10 mass %, more preferably in the range of 1 to 7 mass %, more preferably in the range of 1.5 to 6 mass %, more preferably in the range of 2 to 3 mass %, based on the total mass of the oxide material, wherein metal M is preferably contained in a zeolitic material contained in the oxide material.
[0107] 56. The oxide material according to embodiment 54 or 55, wherein 95 to 100% by mass, preferably 98 to 100% by mass, more preferably 99 to 100% by mass, of the zeolitic material having framework type AEI contained in the oxide material consists of Y, X, O, metal M, and optionally H.
[0108] 57. The oxide material of any one of embodiments 54 to 56, which is the oxide material of embodiment 44.
[0109] 58. Use of an oxide material according to any one of embodiments 43 to 57 as an adsorbent, a molecular sieve, a catalytically active material, a catalyst or a catalyst component, preferably as a catalytically active material, a catalyst or a catalyst component.
[0110] 59. The use according to embodiment 58 for converting C1 compounds to one or more olefins, preferably for converting methanol to one or more olefins, or for converting a synthesis gas comprising carbon monoxide and hydrogen to one or more olefins.
[0111] 60. The use of embodiment 59, wherein the oxide material is an oxide material according to embodiment 43 or any one of embodiments 45 to 53.
[0112] 61. The use of embodiment 58 for the selective catalytic reduction of nitrogen oxides in an exhaust gas stream, preferably an exhaust gas stream from a diesel engine.
[0113] 62. The method of embodiment 61, wherein the oxide material is an oxide material described in embodiment 44 or any one of embodiments 54 to 57.
[0114] 63. A method for catalytically converting C1 compounds to one or more olefins, preferably methanol to one or more olefins, or a synthesis gas comprising carbon monoxide and hydrogen to one or more olefins, the method comprising contacting the C1 compounds with a catalyst comprising an oxide material according to any one of embodiments 43 to 57.
[0115] 64. The method of embodiment 63, wherein the oxide material is an oxide material described in embodiment 43 or any one of embodiments 45 to 53.
[0116] 65. A method for catalytically converting C1 compounds to one or more olefins, preferably methanol to one or more olefins, or a synthesis gas comprising carbon monoxide and hydrogen to one or more olefins, the method comprising producing an oxide material comprising a zeolitic material having framework type AEI and having a framework structure comprising a tetravalent element Y and a trivalent element X and O by the method of any one of embodiments 1 to 42, and contacting the C1 compounds with a catalyst comprising the oxide material.
[0117] 66. The method of embodiment 65, comprising producing an oxide material comprising a zeolitic material having framework type AEI and having a framework structure comprising a tetravalent element Y and a trivalent element X and O by the method of any one of embodiments 1 to 36, and contacting the C1 compound with a catalyst comprising the oxide material.
[0118] 67. A method for selective catalytic reduction of nitrogen oxides in an exhaust gas stream, preferably an exhaust gas stream from a diesel engine, the method comprising contacting the exhaust gas stream with a catalyst comprising an oxide material described in any one of embodiments 43 to 57.
[0119] 68. The method of embodiment 67, wherein the oxide material is an oxide material described in embodiment 44 or any one of embodiments 54 to 57.
[0120] 69. A method for selective catalytic reduction of nitrogen oxides in an exhaust gas stream, preferably an exhaust gas stream from a diesel engine, the method comprising producing an oxide material comprising a zeolitic material having framework type AEI and having a framework structure comprising a tetravalent element Y and a trivalent element X and O by the method of any one of embodiments 1 to 42, and contacting the exhaust gas stream with a catalyst comprising the oxide material.
[0121] 70. The method of embodiment 69, comprising producing an oxide material having framework type AEI and comprising a zeolitic material having a framework structure and a tetravalent element Y and trivalent elements X and O by the method of any one of embodiments 37 to 42, and contacting the exhaust gas stream with a catalyst comprising the oxide material.
[0122] 71. A catalyst, preferably for the selective catalytic reduction of nitrogen oxides in an exhaust gas stream, preferably an exhaust gas stream from a diesel engine, or for the catalytic conversion of C1 compounds to one or more olefins, preferably for the conversion of methanol to one or more olefins, or for the conversion of a synthesis gas comprising carbon monoxide and hydrogen to one or more olefins, comprising an oxide material according to any one of embodiments 43 to 57.
[0123] The present invention will be further described with reference to the following Reference Examples, Comparative Examples and Examples. EXAMPLES
[0124] Reference Example 1.1: Determination of crystallinity The crystallinity of the zeolitic material according to the invention was determined by XRD analysis. X-ray powder diffraction (XRD) patterns were measured using a Rigaku Ultimate VI X-ray diffractometer (40 kV, 40 mA) with CuKalpha (lambda = 1.5406 Angstroms) radiation. An angle range of 2° to 70° (2 theta) was scanned with a step size of 0.02° and the divergence slits were set at a constant opening angle of 0.1°. Quantification of the crystalline content was performed using DIFFRAC.TOPAS V5 software based on the crystal structure, which was refined to fit the data. The model also included linear background, Lorentzian and polarization corrections, lattice parameters, space group, crystallite size. Quantification of the amorphous vs. crystalline content was performed using DIFFRAC.EVA as described in the user manual.
[0125] 1. User Manual DIFFRAC.TOPAS V5, 2014, Bruker AXS GmbH, Karlsruhe, Germany 2. User Manual DIFFRAC.EVA, 2014, Bruker AXS GmbH, Karlsruhe, Germany
[0126] Reference Example 1.2: Determination of the BET specific surface area The BET specific surface area was determined by nitrogen physisorption at 77 K according to ISO 9277, 2010, 2nd edition.
[0127] Reference Example 1.3: Determination of XRD pattern X-ray powder diffraction (XRD) patterns were measured using a Rigaku Ultimate VI X-ray diffractometer (40 kV, 40 mA) using Cu(Kalpha) radiation (lambda = 1.5406 Å).
[0128] Reference Example 1.4: Scanning Electron Microscope Scanning electron microscopy (SEM) experiments were performed on a Hitachi SU-8010 electron microscope.
[0129] Example 1.5: Programmed temperature desorption of ammonia (NH3-TPD) The acidity of the catalysts was measured by temperature programmed desorption of ammonia (NH3-TPD). The catalysts were prepared in a He flow at 450 °C for 60 min, followed by NH3 adsorption at 100 °C for 1 h. After saturation, the samples were purged with a He flow for 3 h to remove the ammonia physically adsorbed on the samples. NH3 desorption was then performed at a heating rate of 5 °C / min from 100 °C to 600 °C. The amount of NH3 desorbed from the samples was detected by a thermal conductivity detector.
[0130] Comparative Example 1: Interzeolitic conversion of zeolite Y to a zeolitic material with framework type AEI a) Preparation of zeolitic materials with framework type AEI Materials used: USY zeolite (SiO2 / Al2O3=26, commercially available from Qilu Huaxin Industry Co., Ltd.) 1.0g Deionized water 0.0g DMPOH solution (as per Example 1a above); 0.23M in water 10.0g Sodium hydroxide (NaOH, AR, 96%, Sinopharm Chemical Reagent Co., Ltd.) 0.24g
[0131] USY zeolite, deionized water, DMPOH solution, and sodium hydroxide were mixed to obtain a synthetic mixture of the following molar composition: SiO21.0:Al2O30.046:Na2O 0.17:DMPOH 0.14:H2O 30
[0132] The synthesis mixture was transferred into a Teflon-lined autoclave oven and crystallized for 3 days at 140° C. After filtering, washing, drying, and calcination at 550° C. for 4 hours, a product designated as a zeolitic material having framework type AEI as shown by XRD analysis was obtained.
[0133] b) Preparation of the H-form of the zeolitic material with framework type AEI prepared in a). The zeolite material prepared in a) was (i) ion-exchanged with 1M NH4NO3 solution (NH4NO3, AR, 99%, Beijing Chemical Reagent Co., Ltd). The filter cake was then washed with deionized water using a Nutsch filter until it was free of nitrates. The ammonium nitrate treatment (i) was then repeated once. The resulting filter cake was dried and then calcined at 550°C for 4 hours. The NH3-TPD curve measured by the method described in Reference Example 1.5 is shown in Figure 1.
[0134] Example 1: Preparation of a zeolitic material with framework type AEI according to the present invention a) Provision of N,N-diethyl-cis-2,6-dimethylpiperidinium hydroxide (DMPOH) Materials used: Cis-2,6-dimethylpiperidine (Sigma-Aldrich Reagent Co., Ltd.) 40g Iodoethane (99%, Aladdin Chemical Co., Ltd.) 222g Potassium bicarbonate (KHCO3, AR, 99.5%, Sinopharm Chemical Reagent Co., Ltd.) 71g Methanol (Sinopharm Chemical Reagent Co., Ltd.) 110g Diethyl ether (AR, 99.5%, Sinopharm Chemical Reagent Co., Ltd.) 1,000g Anion exchange resin (Amberlite IRN-78, OH-type, Thermofisher) 300g
[0135] N,N-Diethyl-cis-2,6-dimethylpiperidine iodide was synthesized by reacting cis-2,6-dimethylpiperidine, iodoethane, and excess KHCO3 in the presence of methanol solvent, followed by refluxing at 70°C for 4 days. After filtering the KHCO3, the solvent and excess iodoethane were removed by rotary evaporation. The product was washed with ether. 1H and 13 The molecular structure was confirmed using C nuclear magnetic resonance (NMR). The product was converted from the iodide form to the hydroxide form (designated DMPOH) using an anion exchange resin.
[0136] b) Preparation of zeolitic materials with framework type AEI Materials used: Sodium aluminate (NaAlO2, AR, 99%, Sinopharm Chemical Reagent Co., Ltd.) 0.038g 4.4g deionized water DMPOH solution (according to a above); 0.23M in water 10g Sodium hydroxide (NaOH, AR, 96%, Sinopharm Chemical Reagent Co., Ltd.) 0.55g Colloidal silica (40% by weight SiO2 in water, Sigma-Aldrich Reagent Co., Ltd.) 2.95 g AEI species (prepared according to Comparative Example 1 above) 0.02 g
[0137] NaAlO2 was dissolved in deionized water, then DMPOH solution was added. After stirring for 2 hours at room temperature, NaOH was introduced, followed by colloidal silica and AEI seeds. This resulted in a synthesis mixture with the following molar composition: SiO2 1.0: Al2O3 0.0083: Na2O 0.35: DMPOH 0.12: H2O 44: AEI zeolite species 0.017
[0138] The ratio of SiO2:Al2O3 was 120:1. After stirring for 10 minutes at room temperature, the synthesis mixture was transferred into a Teflon-lined autoclave oven and crystallized at 140°C for 3 days. After filtering, washing, drying, and calcination at 550°C for 4 hours, a product designated as a zeolitic material with framework type AEI as shown by XRD analysis was obtained.
[0139] c) Preparation of the H-form of the zeolitic material with framework type AEI prepared in b). The zeolitic material prepared in b) was ion-exchanged by (i) 1M NH4NO3 solution treatment. The filter cake was washed with deionized water using a Nutsch filter until it was free of nitrates. The NH4NO3 solution treatment (i) was then repeated once. The resulting filter cake was dried and then calcined at 550°C for 4 hours. The NH3-TPD curve measured by the method described in Reference Example 1.5 is shown in Figure 2. As shown, the NH3-TPD curve shows two peaks centered at about 175°C and 460°C. It is noteworthy that this is different from the NH3-TPD curve obtained for Comparative Example 1 (see above), which proves the structural difference between the zeolitic materials of Example 1 and Comparative Example 1.
[0140] Example 2: Preparation of zeolitic materials with framework type AEI under various conditions The procedure of Example 1 was repeated, except for the following changes, as outlined in Table 1.
[0141] [Table 1]
[0142] As can be seen from Table 1, the selectivity of the desired zeolitic material with framework type AEI can be controlled by adjusting the SiO2 / Al2O3 ratio and the Na2O / SiO2 ratio. In this respect, the zeolitic material with framework type AEI is selectively produced when the SiO2 / Al2O3 ratio is greater than 30:1 and the Na2O / SiO2 ratio is greater than 0.23:1. The XRD patterns of the zeolitic materials with framework type AEI of the experimental runs 6, 11 and 12, determined as described in Reference Example 1.3, are shown in FIG. 3.
[0143] Example 3: Preparation of zeolitic materials with framework type AEI with varying crystallization times The procedure of Example 1 was repeated, except that the crystallization time was changed as follows in hours: (a) 0, (b) 4, (c) 4.75, (d) 5, (e) 5.5, (f) 6, (g) 6.5, (h) 7, (i) 7.5, (j) 8, (k) 10, (l) 72 hours. It was found that the crystallization degree of the AEI zeolite product was continuously improved by extending the crystallization time from 5 hours to 8 hours. After 8 hours, a pure phase of AEI zeolite with high crystallinity was prepared. The crystallization degree did not change after 8 hours, so the crystallization seemed to be completed after 8 hours. In this respect, the crystallization time dependence of the crystallinity of the zeolitic material with AEI framework is shown in FIG. 4. The XRD pattern determined as described in Reference Example 1.3 is shown in FIG. 5. The SEM photograph determined as described in Reference Example 1.4 is shown in FIG. 6.
[0144] Example 4: Preparation of zeolitic material with framework type AEI and containing metal M (Cu) The AEI zeolite materials obtained in Example 1c) and Comparative Example 1b) were each ion-exchanged with 0.1M Cu(NO3)2H2O solution (Sinopharm Chemical Reagent Co., Ltd.) to obtain a copper loading of about 2.4 wt.%, and then calcined at 550°C for 4 h (hereinafter, the obtained materials are referred to as Cu-Example 1) and Cu-Comparative Example 1). In the subsequent tests, fresh and aged copper-containing materials were used, respectively. For the purpose of aging, hydrothermal treatment was performed at 750°C for 16 h with 10% H2O.
[0145] Example 5 Use of zeolitic materials with framework type AEI for selective catalytic reduction of nitrogen oxides The zeolite material obtained in Example 4 was subjected to a selective catalytic reduction test. The catalytic activity in selective catalytic reduction of ammonia (NH3-SCR) was measured in a fixed-bed quartz reactor in a gas mixture containing 500 ppm NO, 500 ppm NH3, 10% O2, and N2 as the balance gas. The gas hourly space velocity (GHSV) was 400000 h -1The results are shown in Figure 7. As can be seen from the catalytic reduction tests, all the tested catalysts showed similar excellent catalytic performance and hydrothermal stability.
[0146] BRIEF DESCRIPTION OF THE DRAWINGS FIG. 1: NH3-TPD curve according to Comparative Example 1b). FIG. 2: NH3-TPD curve according to Example 1c). FIG. 3: XRD patterns of zeolitic materials from Example 2, Table 1, Runs 6, 11 and 12 (a, b and c, respectively). FIG. 4: Dependence of the crystallinity of the zeolitic material according to Example 3 on the crystallization time (determined according to Reference Example 1.1). FIG. 5: XRD patterns of the zeolitic material according to Example 3 crystallized for (a) 0, (b) 4, (c) 4.75, (d) 5, (e) 5.5, (f) 6, (g) 6.5, (h) 7, (i) 7.5, (j) 8, (k) 10, and (l) 72 hours, respectively (determined according to Reference Example 1.3). FIG. 6: SEM micrographs of the zeolitic material according to Example 3 crystallized for (a) 0, (b) 4, (c) 4.75, (d) 5, (e) 5.5, (f) 6, (g) 6.5, (h) 7, (i) 7.5, (j) 8, (k) 10, and (l) 72 hours, respectively (determined according to Reference Example 1.4). FIG. 7: Results from the selective catalytic reduction test of Example 5 are shown.
[0147] References - WO2016 / 080547A1
Claims
1. 1. A method for producing an oxide material comprising a zeolitic material having a framework type AEI and a framework structure comprising a tetravalent element Y, a trivalent element X and an O, comprising: (i) preparing a synthesis mixture comprising water, a source of Y, a sodium-containing source of X, an AEI framework directing agent, and a source of sodium other than said source of X; (ii) heating the synthesis mixture from step (i) to a temperature in the range of 100-180° C. and maintaining said synthesis mixture under autogenous pressure at said temperature range for a time in the range of at least 6 hours to obtain in its mother liquor said oxide material comprising a zeolitic material having framework type AEI and a framework structure comprising tetravalent element Y, trivalent elements X and O, Including, wherein said AEI backbone directing agent according to step (i) comprises an N,N-dialkyl-dialkylpiperidinium cation, which N,N-dialkyl-dialkylpiperidinium cation is an N,N-(C1-C3)dialkyl-(C1-C3)dialkylpiperidinium cation; In the synthesis mixture prepared in step (i) subjected to step (ii), YO 2 The source of Y, calculated as: 2 O 3 The molar ratio of the source of X to the source of X calculated as: 2 :X 2 O 3 and is defined as at least 30:1; In the synthesis mixture prepared in step (i) subjected to step (ii), Na 2 Sodium calculated as YO 2 The molar ratio of Y to the source of Na 2 O:YO 2 and is defined as at least 0.23:
1. Y is Si; X is Al; the source of X comprises sodium aluminate;
2. The N,N-dialkyl-dialkylpiperidinium cation is N,N-(C 1 ~C 2 ) Dialkyl-(C 1 ~C 2 ) dialkylpiperidinium cation, more preferably, the N,N-dialkyl-dialkylpiperidinium cation is N,N-(C 1 ~C 2 ) dialkyl-2,6-(C 1 ~C 2 ) dialkylpiperidinium cation, N,N-(C 1 ~C 2 ) dialkyl-3,5-(C 1 ~C 2 ) dialkylpiperidinium cations, and mixtures of two or more thereof, more preferably N,N-dimethyl-2,6-(C 1 ~C 2 ) dialkylpiperidinium cation, N,N-dimethyl-3,5-(C 1 ~C 2 ) dialkylpiperidinium cations, and mixtures of two or more thereof, more preferably selected from the group consisting of N,N-diethyl-2,6-dimethylpiperidinium cation, N,N-diethyl-3,5-dimethylpiperidinium cation, and mixtures thereof, more preferably the N,N-dialkyl-dialkylpiperidinium cation comprises, more preferably consists of, N,N-diethyl-2,6-dimethylpiperidinium cation, more preferably N,N-diethyl-cis-2,6-dimethylpiperidinium cation; said AEI framework directing agent according to step (i) is preferably a salt, more preferably one or more of a hydroxide and a halide, said halide being preferably one or more of an iodide, a chloride, a fluoride and a bromide, more preferably said AEI framework directing agent according to step (i) comprises a hydroxide, more preferably is a hydroxide; More preferably, the method according to claim 1, wherein said AEI backbone directing agent according to step (i) comprises, preferably consists of, N,N-diethyl-2,6-dimethylpiperidinium hydroxide, preferably N,N-diethyl-cis-2,6-dimethylpiperidinium hydroxide.
3. 3. The method of claim 1 or 2, wherein the source of Y comprises one or more of wet process silica, dry process silica, and colloidal silica, more preferably the source of Y comprises, more preferably consists of, colloidal silica.
4. The source of X is one or more of NaAlO 2 , NaAl(OH) 4 , Na 2 O.Al 2 O 3 , Na 2 A 2 O 4 , Na 5 AlO 4 , Na 7 A 3 O 8 , Na 17 A 5 O 16 , and NaAl 11 O 17 and more preferably, the source of X comprises NaAlO 2 and preferably NaAlO 2 The method according to any one of claims 1 to 3, comprising:
5. 5. The method of any one of claims 1 to 4, wherein the source of sodium other than the source of X comprises, preferably consists of, NaOH.
6. In the synthesis mixture prepared in step (i) subjected to step (ii), Y.O. 2 The source of Y, calculated as: 2 O 3 The molar ratio of the source of X to the source of X calculated as: 2 :X 2 O 3 and is in the range of 30:1 to 600:1, preferably in the range of 40:1 to 500:1, more preferably in the range of 50:1 to 300:1, more preferably in the range of 60:1 to 150:1, more preferably in the range of 60:1 to 100:1, more preferably in the range of 60:1 to 80:1; Y.O. 2 the molar ratio of the source of Y to the AEI framework directing agent calculated as: YO 2 :SDA, which is in the range of 1:1 to 14:1, preferably in the range of 2:1 to 12:1, more preferably in the range of 4:1 to 10:1, more preferably in the range of 7:1 to 9:1; Y.O. 2 The molar ratio of the source of Y to water calculated as: YO 2 :water, in the range of 0.01:1 to 1:1, preferably in the range of 0.01:1 to 0.5:1, more preferably in the range of 0.01:1 to 0.1:1, more preferably in the range of 0.01:1 to 0.05:1; NaO 2 of sodium, calculated as 2 The molar ratio of the source of Y calculated as 2 :YO 2 and is in the range of 0.25:1 to 0.50:1, preferably in the range of 0.27:1 to 0.45:1, more preferably in the range of 0.29:1 to 0.40:1, more preferably in the range of 0.30:1 to 0.35:1; 6. The method according to any one of claims 1 to 5, wherein preferably the synthesis mixture prepared in step (i) and subjected to step (ii) further comprises a crystalline seed material comprising a zeolitic material having framework type AEI and a framework structure comprising tetravalent element Y, trivalent elements X and O.
7. 7. The process according to any one of claims 1 to 6, wherein said temperature in step (ii) is in the range of 120 to 160°C, preferably in the range of 130 to 150°C, and according to step (ii) the synthesis mixture is maintained at said temperature for a time preferably in the range of 6 to 12 hours, more preferably in the range of 6 to 10 hours, more preferably in the range of 7 to 9 hours.
8. (iii) cooling the mixture obtained from step (ii), preferably to a temperature in the range of 10 to 50° C., more preferably in the range of 20 to 35° C.; (iv) separating said oxide material comprising zeolitic material from said mixture from step (ii), said separation preferably comprising: (iv.1) subjecting the mixture obtained from step (ii) to a solid-liquid separation process, preferably comprising filtration or spraying; (iv.2) washing the oxide material, preferably comprising zeolitic material, obtained from step (iv.1); (iv.3) drying said oxide material comprising zeolitic material from step (iv.1) or from step (iv.2), preferably from step (iv.2), preferably in a gas atmosphere having a temperature in the range of 80-170°C, preferably in the range of 100-140°C, more preferably in the range of 100-130°C. A process comprising: (v) calcining said oxide material comprising zeolitic material obtained from step (iv), preferably in a gas atmosphere having a temperature in the range of 400-600° C. Further comprising:
8. The method according to any one of claims 1 to 7, wherein at least a portion of the mother liquor obtained from separating the oxide material from the mixture obtained from step (ii) according to step (iv.1) is preferably recycled to step (i) as part of the synthesis mixture prepared in step (i).
9. (vi) subjecting said oxide material comprising zeolitic material obtained from step (iv) or step (v), preferably from step (v), to ion exchange conditions, preferably ammonium exchange conditions, more preferably comprising contacting said oxide material comprising zeolitic material obtained from step (iv) or step (v), preferably from step (v), with a solution comprising ammonium ions to obtain an oxide material comprising zeolitic material having framework type AEI in its ammonium form, (vii) preferably calcining said oxide material comprising zeolitic material obtained from step (vi) to obtain an oxide material comprising said zeolitic material in its H form.
9. The method of claim 1 , further comprising:
10. (viii) supporting a metal M on the zeolitic material contained in the oxide material, preferably on the zeolitic material contained in the oxide material obtained from step (vi) or step (vii). wherein said metal M is preferably a transition metal from groups 7 to 12 of the periodic system of the elements, more preferably one or more of Fe, Co, Ni, Cu and Zn, more preferably one or more of Fe and Cu, more preferably said metal M comprises Cu, more preferably is Cu.
Citation Information
Patent Citations
Method for producing AEI type zeolite
JP2017036204A
AEI type zeolite, method for prodcuing same, and uses thereof
WO2016080547A1